The difference of anti-inflammatory effect of brown algae extract panida sp. and sargassum sp that is derived from Punaga beach, South Sulawesi - Asmawati Asmawati; Rafikah Hasyim; Andi IA. Lianingsih; Dwi F. Ariani (DiscoverSys Inc., 2016)
Seaweed is one of resourceful plants in Indonesia. Some researchers suggested that brown seaweed has a potential to be an anti-inflammatory agent because it contains polysaccharide sulfate, PUFA, and fuchosantin. Punaga Village that is located in South Sulawesi is an area where most people work as seaweed farmer and cultivation of seaweed. This is why researcher found it interest to use natural sources as an alternative of herbal medicine especially as an anti-inflammatory. The objective of this study was to evaluate the difference of anti-inflammatory effect of brown algae extract Padina sp. and Sargassum sp. that is derived from Punaga Beach, South Sulawesi toward mice. Twenty male mice were used as sample in this study weighing 14-35 g and divided into four groups. Thirty minutes after injection of test material, 0.5 ml pepton 1% is injected into mice leg. The assessment of mice leg use plethysmometer that is taken on the first hour until fourth hour after injection of pepton 1%. Data analysis use T-test to find out the difference of anti-inflamatory effect of brown algae extract Padina sp. and Sargassum sp. The result of this study showed that brown algae extract Padina sp has p<0.05 and brown algae extract Sargassum sp. has p< 0.05 which means that there are anti-inflammatory effect found in both test materials. It is found that brown algae extract Padina sp.has longer anti inflammatory effect half time than in brown algae extract Sargassum sp.